Polyelectrolyte models and molecular dynamics studies of the DNA polymer and DNA-NCP complexes in salt solutions / Ahmad Anggraria Jaya Agung - Ahmad Anggraria Jaya, Agung (2011)
The effects of salt concentration on the flexibility and charge distribution of a DNA chain are probed using MD simulation. For this purpose, the DNA is modeled as 360 negatively charged monomer spheres with radius 10 Å and charge -12 (all in reduced units) linked linearly by a harmonic bonding potential. Each of these spheres represent 6 base pairs. The harmonic force constant kh is determined by balancing the intramolecular and intermolecular forces between 2 monomers separated by an equilibrium bond length of 20.4 Å. This method resulted in good agreement with the experimental contour length and therefore guarantees the reasonableness of the kh parameter. The bending angle force constant kq is determined by relating the chain bending modulus with the experimental DNA persistence length. In a cell, the DNA strand wraps around the so called nucleosome core particle (NCP). In this study, the NCP is represented by a large sphere with radius 35 Å and charge +150. The simulations were performed both with and without the NCP, which when present were 12 in number. The NaCl salt is represented as a charged sphere of radius 2 Å of either +1 or -1 charge modeling a single Na+ or Cl− ion respectively. The salt concentration was chosen to be in the 0.0−0.25 mM range for a DNA concentration of 0.005 mg/ml and in the 0.0−100 mM range for DNA concentration of 2.0 mg/ml. The upper limit corresponded to the maximum computational resources available here. The excluded volume effect was made possible by the application of a purely repulsive 6-12 Lennard-Jones potential and the interaction between charges was strictly Coulombic, where the Ewald summation was computed by the P3M method. The results show that the NaCl salt concentration within the cell play a significant role in determining the DNA conformation, as well as the strength of the DNA-NCP and DNA-ions interaction. Some theoretical equations for calculating the polyelectrolyte persistence length seem to disagree with the simulation results. A new concept that leads to the "ionic bridging effect" is introduced and shown to be important in determining the DNA topology. By the RDF data, it is shown that the classical PB cylindrical cell model neglects the counterion condensation at monomer neighbors. The above results all imply the importance of molecular simulations in obtaining information which cannot so readily be made available from experiments.